2019
DOI: 10.3390/ijerph16183400
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Effects of Congestion on Traffic Accidents

Abstract: Traffic accidents impart both economic and social costs upon communities around the world, hence the desire for accident rates to be reduced. For this reduction to occur, the factors influencing the occurrence of accidents must be understood. The role of congestion in modifying accident risk has been widely studied, but consensus has not been reached, with conflicting results leaving open questions. An inverse relationship between accidents and congestion would imply a benefit of congested conditions for road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 53 publications
3
51
0
2
Order By: Relevance
“…Studies reviewed by Retallack and Ostendorf [22] using two-three million hourly traffic measurements reported concave non-linear responses. The 5.2 million data points used in this study represent a significant increase, supporting the observation that large amounts of high-quality data allow more detailed relationships to be uncovered [22]. High temporal resolution traffic data allows the precise identification of traffic conditions at the time of each accident.…”
Section: Relationship Between Traffic Volume and Accident Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reviewed by Retallack and Ostendorf [22] using two-three million hourly traffic measurements reported concave non-linear responses. The 5.2 million data points used in this study represent a significant increase, supporting the observation that large amounts of high-quality data allow more detailed relationships to be uncovered [22]. High temporal resolution traffic data allows the precise identification of traffic conditions at the time of each accident.…”
Section: Relationship Between Traffic Volume and Accident Frequencymentioning
confidence: 99%
“…A strong understanding of this relationship is necessary to improve traffic management and reduce accident frequency. Research stems from the 1930s [11], with relationships between accident occurrence and traffic volume/congestion falling into one of two broad categories: linear and non-linear [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among the main factors behind traffic accidents are environmental conditions (weather, visibility, etc. ), road characteristics, vehicle design, human error, and the volume of vehicles circulating on our roads ( Retallack and Ostendorf, 2019 ). In some cases, traffic accidents are due to a combination of more than one of the above.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of traffic accidents occurring increases with the volume of vehicles on our roads and in line with certain road characteristics ( Cadar et al, 2017 ; Martin, 2002 ; Wang et al, 2013a ). This probability increases in situations characterized by both low and high levels of congestion ( Retallack and Ostendorf, 2019 ; Sun et al, 2016 ; Wang et al, 2013b ; Zhou and Sisiopiku, 1997 ). In the latter case, however, the severity of the resulting accidents tends to fall when vehicles crash at lower speeds ( Casado-Sanz et al, 2020 ; Shefer, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhan-Moodie [17] concluded that congestion can be linked with crashes by superimposing crash areas on top of congested areas using GIS shapefiles. Retallack and Ostendorf [18] reviewed this work and concluded that the method was not tested using congestion information that pertained at the time of the crash. The study presented here addresses this issue by using a congestion measure that is predicated on the traffic conditions at the time of the crash.…”
Section: Literature Reviewmentioning
confidence: 99%